A simple echocardiographic score to rule out cardiac amyloidosis. (23rd November 2020) - Aimo, Alberto; Chubuchny, Vladyslav; Vergaro, Giuseppe; Barison, Andrea; Nicol, Martin; Cohen‐Solal, Alain; Castiglione, Vincenzo; Spini, Valentina; Giannoni, Alberto; Petersen, Christina; Taddei, Claudia; Pasanisi, Emilio; et al.
Abstract: Background: Early diagnosis of cardiac amyloidosis (CA) is warranted to initiate specific treatment and improve outcome. The amyloid light chain (AL) and inferior wall thickness (IWT) scores have been proposed to assess patients referred by haematologists or with unexplained left ventricular (LV) hypertrophy, respectively. These scores are composed of 4 or 5 variables, respectively, including strain data. Methods: Based on 2 variables common to the AL and IWT scores, we defined a simple score named AMYLoidosis Index (AMYLI) as the product of relative wall thickness (RWT) and E/e′ ratio, and assessed its diagnostic performance. Results: In the original cohort (n = 251), CA was ultimately diagnosed in 111 patients (44%). The 2.22 value was selected as rule‐out cut‐off (negative likelihood ratio [LR−] 0.0). In the haematology subset, AL CA was diagnosed in 32 patients (48%), with 2.36 as rule‐out cut‐off (LR− 0.0). In the hypertrophy subset, ATTR CA was diagnosed in 79 patients (43%), with 2.22 as the best rule‐out cut‐off (LR− 0.0). In the validation cohort (n = 691), the same cut‐offs proved effective: indeed, there were no patients with CA in the whole population or in the haematology or hypertrophy subsets scoring < 2.22, <2.36 or < 2.22, respectively. Conclusions: The AMYLI score (RWT*E/e′) may have a role as an initial screening tool for CA. A < 2.22 value excludes the diagnosis in patients undergoing a diagnostic screening for CA, while a < 2.36 and a < 2.22 value may be better considered in the subsets with suspected cardiac AL amyloidosis or unexplained hypertrophy, respectively.